Matriculacion y trabajo infantil en Bolivia: Un análisis quasi experimental - Diego Alejandro Vera Cossío (Institute for Advanced Development Studies (INESAD), 2011)
– This paper contributes with evidence about the ex post impact to the program of conditional cash transfer program Bono Juancito Pinto in public schools in Bolivia. In order to correctly identify the potential beneficiaries and avoid problems of endogeneity and selection bias, we evaluate the effect of the announcement of the bonus on enrollment and child labor through a quasi experiment using data from household surveys. By estimating bivariate probit models is that the announcement of this bond, in general, has had no effect in terms of enrollment, with only disaggregated effects for young children. At the same time, there were no significant effects on child labor, both results do not change when replicating the analysis by income quintiles, although there are differences in the case of rural areas. These results close a gap in the literature regarding the evaluation of the Bono and make possible discussions in pursuit of better targeting.
Keywords: I21; I38; J13; J22; 330; Conditional transfers; Child Labour; Economics of Education